2023
DOI: 10.3390/polym15122697
|View full text |Cite
|
Sign up to set email alerts
|

Porous Geopolymer/ZnTiO3/TiO2 Composite for Adsorption and Photocatalytic Degradation of Methylene Blue Dye

Abstract: In this study, GP (geopolymer) and GTA (geopolymer/ZnTiO3/TiO2) geopolymeric materials were prepared from metakaolin (MK) and characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscopy (SEM), energy dispersive X-rays (EDX), specific surface area (SSA), and point of zero charge (PZC). The adsorption capacity and photocatalytic activity of the compounds prepared in the form of pellets was determined by degradation of the methylene blue (MB) dye in batch reactors, at pH = 7.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Adsorption kinetics studies help to determine a suitable adsorbent material, predict the required contact time, and optimize the operating conditions to achieve efficient dye degradation ( Ghaffar et al, 2023 ; Usman et al, 2023 ). The kinetics of dye degradation through adsorption involves understanding the rates at which dye molecules are adsorbed onto the adsorbent materials and can be described using various mathematical models, with the most commonly used types being the pseudo-first-order and pseudo-second-order kinetics ( Borah et al, 2023 ; Jaramillo-Fierro et al, 2023 ; Singh et al, 2023 ; Usman et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption kinetics studies help to determine a suitable adsorbent material, predict the required contact time, and optimize the operating conditions to achieve efficient dye degradation ( Ghaffar et al, 2023 ; Usman et al, 2023 ). The kinetics of dye degradation through adsorption involves understanding the rates at which dye molecules are adsorbed onto the adsorbent materials and can be described using various mathematical models, with the most commonly used types being the pseudo-first-order and pseudo-second-order kinetics ( Borah et al, 2023 ; Jaramillo-Fierro et al, 2023 ; Singh et al, 2023 ; Usman et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…From all the adsorption test results, we observed that the FM-TiO2 has a larger adsorption capacity than the FM, which suggests that applying TiO2 to the geopolymer may enhance its adsorption capacity [58]. As a result of their porous structures and the presence of active sites on their surfaces, the FM and FM-TiO2 composites both exhibit adsorption capabilities [58]. In our previous study [13], we modified a metakaolin /cement kiln dust -based geopolymer composite to remove organic reactive dye effluent from wastewater by two different methods: adsorption and solidification of organic pollutants inside the geopolymer matrix.…”
Section: -Effect Of Timementioning
confidence: 90%
“…The decolorization rate for the FM geopolymer composite at 120 minutes is 80.22%, while it is 89.56% for the FM-TiO2 geopolymer composite. From all the adsorption test results, we observed that the FM-TiO2 has a larger adsorption capacity than the FM, which suggests that applying TiO2 to the geopolymer may enhance its adsorption capacity [58]. As a result of their porous structures and the presence of active sites on their surfaces, the FM and FM-TiO2 composites both exhibit adsorption capabilities [58].…”
Section: -Effect Of Timementioning
confidence: 90%